The anxious middle : planning for the future of the Christian college - Ream, Todd C.; Pattengale, Jerry A. (Baylor University Press, 2023)
"Engages Dietrich Bonhoeffer's writings and Western Christian history to offer resources and strategies for Christian colleges and universities to address the current crisis of Christian higher education"--